Assessment of Plankton Diversity with Reference to Monthly and Seasonal Variation in the Godavari River, Andhra Pradesh - Rao, N. Veerabhadra; Kumar, M. Kishore; Kalavathi, N. R. (International Journal of Economic Plants, 2025)
The diversity of plankton in the Godavari River was studied from April, 2021 to March, 2022 across six sampling stations: Kunavaram, Rajamahendravaram, Dowleswaram, Kovvur, Tallapudi, and Polavaram to investigate monthly and seasonal variations of planktons in the Godavari River ecosystem. The study revealed significant temporal variations in both phytoplankton and zooplankton diversity, reflecting the ecological responses to changes in nutrient load, water flow, and anthropogenic pressures. A total of 25 phytoplankton species were identified, comprising 12 species of Chlorophyceae (5 families), 9 species of Bacillariophyceae (4 families), 3 species of Cyanophyceae (2 families), and 1 species of Euglenophyceae (1 family). Among these, Chlorophyceae was the dominant group recorded at all stations throughout the study period. Additionally, 26 zooplankton species were recorded, representing 6 groups, 12 families, and 21 genera. These included 8 species of Rotifera, 6 of Cladocera, 5 of Crustacea, 4 of Copepoda, and 1 of Ostracoda, with Rotifera being the most dominant group (30.76%). Monthly and seasonal variations in zooplankton populations were assessed, with the highest density (81.33±7.50 no. l-1) observed during the hot weather season of 2023 at Rajamahendravaram, and the lowest (42.00±4.25 no.l-1) during the South-West Monsoon at Polavaram. The composition and abundance of planktonic communities indicated that the Godavari River supporteda moderately rich and productive aquatic ecosystem. Moreover, the observed diversity patterns establish plankton as valuable bioindicators for assessing water quality and ecological health across different stretches of the river. Continuous monitoring was essential for biodiversity conservation and sustainable river management.